RESOLUTION OF VIDEO ECOLOGY ISSUE IN THE REGION OF CAUCASIAN MINERAL WATERS - Natalya Viktorovna Barabash; Sofia Ilinichn Aslanova (Современная наука и инновации)
Pyatigorsk, Kislovodsk, Essentuki, Zheleznovodsk belong to the ecological and resort region - the Caucasian Mineral Waters, where great importance is given to the preservation and protection of the natural environment. However, recently the issue of the negative, as well as aggressive influence of the surrounding modern architectural environment on the person's well-being became very topical. This is the issue of the division of ecology aimed at studying the visual and aesthetic components of the urban environment -videoecology. The subject of research in this scientific article are problems associated with visual pollution of the urban environment.